A Computational Drug Repositioning Effort Using Patients' Reviews Dataset - Akkaya, Ali; Bakal, Gokhan (Institute of Electrical and Electronics Engineers Inc., 2023)
The drug discovery process is one of the core motivations in both medical and, specifically, pharmaceutical disciplines. Due to the nature of the process, it requires an excessive amount of time, clinical experiments, and budget to cover each discovery phase. In this sense, computational drug discovery efforts can shorten the discovery process by providing plausible candidates since many of the attempts fail for several reasons, such as a lack of participants, financial problems, or ineffective results. In this study, the goal is to identify plausible candidate drugs for diseases. To do that, we utilize a personal experience of drugs dataset generated by patients. Beyond the user-generated comments, the users also give a rate between 1 and 10. Since we want to ensure the dataset quality, we first performed sentiment analysis experiments to prove that the reviews/comments are consistent with the given rating score. Then, only the review pairs having an effectiveness rate of 6 or more are selected as pre-filtered drug-disease pairs. We also build a knowledge graph using treatment-related biomedical relations using predications from Semantic Medline Database to identify drug similarities utilizing the Simrank similarity algorithm. As a result, we reported a list of plausible drugs as repurposing/repositioning candidates for further experiments. © 2023 Elsevier B.V., All rights reserved.
Aselsan; CIS ARGE; Yeditepe University
Keywords: Computational Drug Repositioning; Machine Learning; Sentiment Analysis; Simrank Similarity; Bioinformatics; Budget Control; Machine Learning; Quality Control; Semantics; Clinical Experiments; Computational Drug Repositioning; Drug Discovery; Drug Discovery Process; Drug Repositioning; Financial Problems; Machine-Learning; Sentiment Analysis; Simrank; Simrank Similarity